(untitled) (Journal of Legal Studies, 2017)
oth in the European Union and in European doctrine was widely discussed the ratione materiae of the future European Public Prosecutor. In terms of the Lisbon Treaty its jurisdincion is limited to crimes that threaten the Union’s financial interests, but at the same time the Council of Europe may extend this competence by unanimous decision and other serious offenses. European Public Prosecutor is now one of the main objectives of the European Union and is one of the priorities of the common space of freedom, security and justice for the next five years. Still looking for ways and methods useful for the implementation of these goals, but two conditions must be met: it must be a useful institution, well embedded in the EU institutions and must be based on our national legal traditions that have proven their relevance. Finally, it gives a substantial importance to defense lawyers and rights in various stages of the procedure, both in the contentious matter of freedom and during the performance of an adversarial procedure.